Comparative Assessment of Tumor Marker Profiles in Colon Cancer and Benign Neoplasms: A Clinical Study in Nineveh Province - Obaid Mostafa, Shaimaa; Al-Hayali, Haitham L.; K. Hasan, Mowafak (Journal of Neonatal Surgery, 2025)
Background: Colon cancer is one of the deadliest forms of cancer spread worldwide. it often begins without symptoms, its symptoms in the early stages are similar to those of intestinal disorders and other diseases. And spreads to organs like the liver and pancreas. Also, there is a difference in the incidence of tumors in males compared to females. Detecting it early can make a significant difference in how well patients respond to treatment and survival. Objectives: This study seeks to identify tumor parameters that help differentiate between benign and malignant tumors, detect the different stages of malignant tumors, and distinguish between male and female tumors. Methods: Blood samples were gathered from 128 individuals undergoing colonoscopies in hospitals across Mosul. And healthy persons too. Based on biopsy results, the tumors were categorized as benign or malignant. and After colectomy, the malignant tumor samples were divided into three groups depending on the tumor stages. Blood was taken before the procedure and tested using the ELISA method. with comparison groups including healthy individuals. Results: The findings showed Clear differences between the sexes. Males had significantly lower blood counts. and weakened immunity. the ratios such as L/M and P/L showed meaningful differences between men and women, Which provides differences in the immune system response of patients according to gender. In women had higher levels of tumor markers—especially in early-stage cancer. Markers like Septin-9, HIF-1α, and cf-DNA showed significant differences by tumor stage in women, while they were more accurate in men in identifying colon cancer progression. The benign tumor groups showed moderate levels of tumor markers. Conclusion: The diagnosis and development of colon cancer can be understood with the help of VCAM-1, Septin-9, HIF-1α, CDH-17, cf-DNA, and CRP. cf-DNA and HIF-1α are capable of differentiating between various forms of malignancies and benign tumors, distinguishing factors such as sex and tumor stages.